Pengaruh Sikap Keuangan terhadap Perilaku Pengelolaan Keuangan dengan Literasi Keuangan sebagai Variabel Mediasi - Mariani, I Gusti Agung Ayu; Sawitri, Ni Putu Yuliana Ria; Geriadi, Made Ayu Desy (BUDGETING : Journal of Business, Management and Accounting, 2024)
In the current era of globalization, personal financial management has become very important due to rising living costs and increasingly complex needs. Students, as the younger generation easily influenced by globalization, are prone to consumptive behavior and lack awareness and knowledge about good financial management. This study aims to analyze the influence of financial attitudes on financial management behavior with financial literacy as a mediating variable among students of the Faculty of Economics and Business at Ngurah Rai University. Using a quantitative approach and secondary data, this study involved 250 active students from the 2020-2023 cohorts as samples taken through stratified proportionate random sampling techniques. Data analysis was performed using the Partial Least Square (PLS) method. The results showed that financial attitudes have a positive and significant effect on financial literacy (H1), financial literacy has a positive and significant effect on financial management behavior (H2), and financial attitudes have a positive and significant effect on financial management behavior (H3). Additionally, financial literacy acts as a mediator in the influence of financial attitudes on financial management behavior (H4). These findings indicate that individuals with positive financial attitudes tend to have higher levels of financial literacy, which in turn influences better financial management behavior. This underscores the importance of increasing financial literacy and fostering positive financial attitudes to enhance students' financial management behavior, ultimately helping them manage personal finances more effectively and avoid financial problems in the future. Keywords: Financial Attitudes, Financial Literacy, Financial Management Behavior.